2015
DOI: 10.5433/1679-0359.2015v36n1p391
|View full text |Cite
|
Sign up to set email alerts
|

Características morfogênicas, estruturais e produtivas de acessos de capim-buffel

Abstract: ResumoEmbora o capim-buffel seja tão importante para os sistemas produtivos no semiárido brasileiro, estudos com essa forrageira são ainda escassos e pouco difundidos, dessa forma conduziu-se este experimento com o objetivo de avaliar as características morfogênicas, estruturais e produtivas de seis acessos de capim-buffel (Cenchrus ciliaris L.) pertencentes ao banco ativo de germoplasma (BAG) da Embrapa semiárido. O experimento foi realizado no Departamento de Tecnologia e Ciências Sociais (DTCS) da Universid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…These values are lower than those found by Moreira et al (2015) for the same cultivar of buffel grass, with a SnR of 127 mm day -1 , likely due to the plants being evaluated for a longer period in the present study (70 days).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…These values are lower than those found by Moreira et al (2015) for the same cultivar of buffel grass, with a SnR of 127 mm day -1 , likely due to the plants being evaluated for a longer period in the present study (70 days).…”
Section: Resultscontrasting
confidence: 54%
“…OB was remarkable regarding this variable, which allowed greater fluxes of leaf growth and lifespan, characteristics that are determined by NPK levels in the soil, with N mainly impacting on the expression of morphogenic variables leading to an increase in LER, and with K increasing the leaf length (LL) (HODGSON, 1990). Moreira et al (2015) found a mean LL of 17.53 days, while evaluating the morphogenic characteristics of six buffel grass accessions in a period of 70 days. The lower LL found in the present study is also associated with the shorter evaluation period, considering 30% inflorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Only the leaf blade width of Andropogon grass was affected by the regrowth period adjusted to the positive linear equation, with an increase of 68.81% from 21 to 63 days. According to Moreira et al (2015), leaf length and width are decisive factors in establishing the leaf area, allowing a greater interception of light and consequently higher photosynthesis rates.…”
Section: Cultivarsmentioning
confidence: 99%
“…With the increase in the vulnerability of agricultural production due to the expansion of semiarid areas and the increase in the global demand for animal products, it is necessary to adopt strategies that make animal production feasible in semiarid regions (MARENGO, 2008;IPCC, 2014). The development and growth of the forage plant vary according to the growth stage, species, cultivar and availability of abiotic growth factors (DARTORA et al, 2013;MOREIRA et al, 2015;MARANHÃO et al, 2018a). It is emphasised that rainfall is the main abiotic modulator of growth of forages under rainfed conditions, since it is commonly seen as an abiotic factor that is more limiting to plant growth and development in semiarid regions.…”
Section: Introductionmentioning
confidence: 99%